Peran Patroli Roda Empat Dalam Upaya Pencegahan Tindak Pidana Pencurian Dengan Kekerasan Oleh Satuan Sabhara Polresta Cirebon - Maulana, Yusuf (Police Studies Review, 2020)
The background of this research problem is the acts of theft with violence that often occur in the Cirebon Regency. This study discusses the description of criminal acts of theft with violence in Cirebon Police, the role of Sabhara Unit patrols in preventing criminal acts of theft with violence in the Cirebon Police area, and the factors that influence the vigorous implementation of four-wheeled patrols of Sabhara Unit in efforts to prevent criminal acts of theft with violence in the Cirebon Police jurisdiction. This study uses a qualitative approach and data collection techniques by interviewing, observing, and studying documents. The research location was carried out in the Cirebon Police Region. The theory used in this research is the theory of routine activities and management theory, while the concept used is the concept of patrol, four-wheeled patrol, and theft with violence. The results showed that theft by violence was classified as a large number of criminal acts and the settlement of the case was still lacking. This is because there are deficiencies in the implementation of four-wheeled patrols, especially personnel, hard-to-reach areas and inadequate budgets. Cirebon Police conduct prevention efforts through Sabhara Patrol. Based on research conducted by the author, the problem of four-wheeled patrol is human resources, both from the police and from the community. The obstacle factor in the implementation of four-wheeled patrols is the lack of patrol personnel, the lack of fuel subsidies to support the implementation of patrols and the community itself does not want to participate in patrol implementation, especially to provide information about the situation and conditions around the environment. In addition, the vast area of ​​Cirebon Regency has resulted in several areas not yet reached by four-wheeled patrols. Suggestions can be given (1) Increasing the intensity of patrols in vulnerable areas and at hours prone to violent thieves, (2) Providing a budget to patrol at the beginning of the month so that patrol members no longer worry about unwanted problems in patrolling, (3) conducting training of Sabhara Unit personnel every six months so that personnel can understand the tasks and understand the proper implementation of patrols, (4) For patrol leaders it is recommended to use Whatsapp application for supervision of patrol implementation with video call feature so that members cannot lie in conducting patrols, (5) Utilization of timestamp camera applications in the documentation of patrol activities so that documentation can be held accountable to the leadership for its truthfulness.